ヒガシ ナンキョク エンガン ニオケル 1976ネン トウキ ノ シゴメン カンキョウ ダイ1カイ ナンキョク キスイケン シンポジウム - 井上, 治郎; イノウエ, ジロウ; 中島, 暢太郎; ナカジマ, チョウタロウ; INOUE, Jiro; NAKAJIMA, Chotaro (国立極地研究所, 1979)
P(論文) 東南極大陸の斜面から沿岸にいたる地域の大気循環を,主として1976年冬の昭和基地周辺について考察した.同じ東南極でも,トラフやリッジの位置によって,時間と場所で子午面循環の様子が非常に異なっている.昭和基地の対流圏上部では,冬の卓越風は西～南西風であるが,風速は南風の時に大きくなり,一時的な渦輸送も,定常的な渦輸送と同じく大気の南北交換に重要であることがわかった.波動の振幅が増大する時は,ブロッキング高気圧が作られやすく,北東風の頻度も増すことが確かめられた.対流圏下部では,大部分が海から内陸へ向かう北成分の風であり,特に,900mb付近に風速の極大値をもつことが多い.このことに関しては,昭和基地の東の地形の効果が考えられる. The circulation of the atmosphere over the East Antarctic periphery is discussed mainly on the basis of the data of Syowa Station during the polar night of 1976. According to the location of a through or a ridge, the meridional circulation changes with time and place. In the upper troposphere over Syowa the prevailing wind is W-SW in the winter, while the southerly wind increases its speed. It is pomted out that trasient eddy transportation is as well significant as the standing one for the meridional air mass exchange. The blocking high formed in the meridionally developed wave contributes to the increase of the NE wind. In the lower troposphere the major part is occupied by the northerly component having a maximum wind speed around 900 mb. Effects of topography east of the station are inferred. departmental bulletin paper